Preparation of immobilized lipase by modified polyacrylonitrile hollow membrane using nitrile-click chemistry. (February 2019) - Li, Youran; Wang, Hanrong; Lu, Jiawei; Chu, Alex; Zhang, Liang; Ding, Zhongyang; Xu, Sha; Gu, Zhenghua; Shi, Guiyang
Graphical abstract: Highlights: PAN was modified using nitrile-click chemistry for enzyme immobilization. PAN-PEI showed strong interaction with the hydrophilic surface of enzyme protein. SA and CaCl2 further improved the immobilization effect. The activity of immobilized lipase was 2.5 times higher than Novozym® 435. Abstract: The application of immobilized lipase in the enzymatic production of biodiesel has shown numerous advantages. In this study, surface of Polyacrylonitrile (PAN) hollow membrane was first modified using nitrile-click chemistry in order to fit for interaction with enzyme proteins. Then sodium alginate (SA) was introduced and the membrane was post-treated by CaCl2 . When the prepared PAN-PEI-SA-CaCl2 was used for lipase immobilization, the protein loading was 36.90 mg/g, and the enzyme activity reached up to 54.47 U/g, which was 2.5 times as much as that of Novozym® 435. As a result, the constructed immobilized lipase obtained a maximum biodiesel yield of 78.5%, which was 2.4 times that of the Novozym® 435 in transesterification reactions. Moreover, the biodiesel yield decreased by only 11% after the immobilized enzyme was continuously used for 20 times. This study exhibits that this technic has broad application prospects in the field of conversion of biomass resources.